Permutation tests: Are there differences in product liking? - Michael Meyners (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2000)
The target of our considerations is whether or not we can find significant differences between subgroups of consumers with respect to given hedonic variables. For this purpose a STATISconsensus is computed for each group and the dissimilarities between groups are judged with the help of the RV-coefficient. Since the distribution of this coefficient is unknown and we do not make any assumptions on the distribution of the error terms, a permutation test is performed. This provides a simple possibility to test for significance of the dissimilarities in question. Some pre-treatment of the data is necessary to perform this statistical test, afterwards subgroups according to the two sets of consumer tests, the different geographies and some of the classification variables within consumer test 1 are considered. Whenever we find significant dissimilarities a graphical representation of the respective consensuses is provided to interpret the differences.
Keywords: 519